Marine Gastropod Planaxis sulcatus (Born, 1778) of Uvari Coastal Waters: A Comprehensive Study on Its Antibacterial Activity, Biochemical Composition and FTIR Spectroscopy - J.Jenifer; Renuga, F. Brisca (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Diverse nutritional profiles and potent antimicrobial properties distinguish marine gastropods from other members of the phylum Mollusca. This study targets the investigation of the antibacterial activity, biochemical and FTIR analysis of ethanol extracts of marine gastropod mollusc Planaxis sulcatus. The well diffusion method was used to carry out the antibacterial assay. The extract showed the maximum inhibition (21±2 mm inhibitory zone) against the human bacterial pathogen S. aureus, whereas K. pneumonia showed the lowest susceptibility (12 mm). The extracts had MIC values between 0.21 and 1.04 mg/ml. The biochemical assay's findings revealed that the majority of the snail's flesh (51%) is made up of protein, with only 5% of the mass coming from carbohydrates and very trace amounts of fat (0.2%). The FTIR analysis represents the presence of alkyl halides, nitro compounds, aromatic compounds, alkynes, nitriles, carboxylic acid, aldehyde, alkanes and alcohol in the gastropod extracts. The aforementioned observational result demonstrates the abundance of antibacterial substances in the gastropod extracts. Further research is necessary to fully understand the structural composition of the antibacterial substances found in this marine snail.